The effect of trust and relationship commitment on supply chain performance through integration and collaboration - Kun Jang; Joonkyum Lee (Global Business & Finance Review (GBFR), 2022)
Purpose: This study analyzed the effects of supply chain management trust and relationship commitment on financial and non-financial performance, focusing on the mediating effect of supply chain management integration and collaboration. Design/methodology/approach: This study was designed as a conceptual research model to verify the mediating effect of integration and collaboration in the relationship trust and relationship commitment and supply chain performance. In order to design a conceptual research model, a total 30 items were investigated and the SEM method was verified using six observations variables Findings: According to this study, it was found that financial and non-financial performance of companies adopting Korea's supply chain management increased when trust and relationship commitment were strengthened with partner companies. In particular, in the relationship between trust of supply chain management and supply chain management performance, integration with partner companies contributed to increase financial performance, but did not make a positive contribution to non-financial performance. On the other hand, in the relationship between supply chain management's relationship commitment and supply chain management, collaboration made a positive contribution to increasing financial and non-financial performance. What this study means is that higher trust and relationship commitment with partner companies in supply chain management contributed to a direct influence on financial and non-financial performance. Research limitations/implications: This study used the citation count to measure the effect of trust and relationship on supply chain performance. While this serves the purpose of this study, citation counts may not perfectly represent the value and impact of a study. The findings of this study provide a guide post for future studies. Originality/value: This study provides an updated, comprehensive literature review of the overall development, contributions and limitations of forecasting studies in the supply chain management fields. The researchers can see the subjects and types of research that already conducted and which topics remain unexamined.
Keywords: 650; Supply chain management; Trust and Relationship commitment; Supply chain performance; Mediation effect